Determinants of nitrogen use efficiency in coffee crops. A review - Sadeghian-Khalajabadi, Siavosh; Acuña-Zornosa, José-Ricardo; Salazar-Gutiérrez, Luis-Fernando; Rey-Sandoval, Juan-Camilo (Revista de Ciencias Agrícolas, 2022)
World production of coffee (Coffea spp.) has increased in recent decades due to its growing demand. Nitrogen (N) is one of the most required nutrients by coffee crops and in many cases, the most yield-limiting; nevertheless, a high percentage of supplied N is lost, generating pollution, greenhouse gases, and economic losses. Given this scenario, it is a priority to adopt practices that increase nitrogen use efficiency related to the capacity of plants to absorb and use N to produce biomass. This article provides context about NUE and determining factors in coffee: plant, soil, climate, and management. On the plant side, despite advances in genetics and the results of genotype evaluation, it may be a decade or more before improved coffee varieties with high EUN become available or used in world coffee farming. Both the physical, chemical, and biological properties of the soil and the elements of the climate, mainly temperature, precipitation, and solar radiation, have an influence on coffee growth and many of the processes that intervene in the N cycle and NUE; however, some components of these two factors are not fully controllable. Management of the factors that determine NUE should focus on reducing N losses in the system, increasing its uptake and utilization by plants, and maintaining or increasing productivity.